Is prophylaxis required for delivery in women with factor VII deficiency?. (22nd April 2013) - Baumann Kreuziger, L. M.; Morton, Colleen T.; Reding, Mark T.
Summary: Factor VII (fVII) deficiency is a rare congenital bleeding disorder in which fVII activity level and bleeding tendency do not completely correlate. Pregnancy and delivery present a significant haemostatic challenge to women with fVII deficiency. Treatment with recombinant factor VIIa (rfVIIa) carries a thrombotic risk and the literature is not clear whether prophylaxis is necessary prior to delivery. The aim of this study was to define management, haemorrhagic and thrombotic complications of pregnant women with fVII deficiency through a systematic review. Medical databases (PubMed, MEDLINE, CINAHL, Academic Search Premier, Cochrane Library, Web of Science and Scopus) were searched using "factor VII deficiency" and "pregnancy" or "surgery." Overall 34 articles, four abstracts, and three institutional cases were reviewed. Literature from 1953 to 2011 reported 94 live births from 62 women with fVII deficiency. The median fVII activity was 5.5%. Haemostatic prophylaxis was used in 32% of deliveries. Without prophylaxis, 40 vaginal deliveries and 16 caesarean sections were completed. The odds of receiving prophylaxis were 2.9 times higher in women undergoing caesarean section compared to vaginal delivery. Post‐partum haemorrhage occurred in 10% of deliveries with prophylaxis and 13% of deliveries without prophylaxis. The fVII level did not significantly differ between women who did and did not receive prophylaxis. We present the only systematic review of the management of pregnancy in fVII deficient women. No difference in post‐partum haemorrhage was seen in deliveries with and without prophylaxis. Therefore, we recommend that rfVIIa be available in the case of haemorrhage or surgical intervention, but not as mandatory prophylaxis.